Mrs. Frisby and the rats of NIMH - O'Brien, Robert C. (New York Aladdin Paperbacks, 1986)
Having no one to help her with her problems, a widowed mouse visits the rats whose former imprisonment in a laboratory made them wise and long lived.
Keywords: Mice -- Fiction; Rats -- Fiction